2023
DOI: 10.3390/toxins15100617
|View full text |Cite
|
Sign up to set email alerts
|

Smart-seq2 Technology Reveals a Novel Mechanism That Zearalenone Inhibits the In Vitro Maturation of Ovine Oocytes by Influencing TNFAIP6 Expression

Zongshuai Li,
Yali Liu,
Tian Ma
et al.

Abstract: Zearalenone (ZEN), a non-steroidal estrogenic fungal toxin widely present in forage, food, and their ingredients, poses a serious threat to animal and human reproductive health. ZEN also threatens ovine, a major source of human food and breeding stock. However, the mechanisms underlying the impact of ZEN on the in vitro maturation (IVM) of ovine oocytes remain unclear. This study aimed to elucidate these mechanisms using the Smart-seq2 technology. A total of 146 differentially expressed genes were obtained, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It has a stable structure, is not easily degradable, is widely distributed, can be present at any stage of crop processing, and easily contaminates various grains [ 4 , 5 , 6 ]. It poses a threat to the livestock breeding industry (pigs, sheep, and cows) [ 7 , 8 , 9 , 10 ], as well as human reproductive health. Therefore, it is of great importance to determine the mechanism of toxicity of ZEN and screen for effective antagonistic drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a stable structure, is not easily degradable, is widely distributed, can be present at any stage of crop processing, and easily contaminates various grains [ 4 , 5 , 6 ]. It poses a threat to the livestock breeding industry (pigs, sheep, and cows) [ 7 , 8 , 9 , 10 ], as well as human reproductive health. Therefore, it is of great importance to determine the mechanism of toxicity of ZEN and screen for effective antagonistic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of Smart-seq2 technology and preliminary results of this study showed that ZEN could increase oxidative stress, interfere with the spindle assembly and cell autophagy, and ultimately inhibit ovine oocyte maturation by affecting the expression of genes related to apoptosis, oxidative stress, autophagy, oocyte maturation, and spindle assembly [ 10 ]. Therefore, a constantly updated natural plant compound library and the screening of antagonistic drugs were combined in this study, focusing on two types of substances: antioxidants and autophagy inhibitors.…”
Section: Introductionmentioning
confidence: 99%